Local versus Spinal Anesthesia for Endovenous Ablation Therapy: A Comparative Study - Berk Arapi; Çiğdem Tel Üstünışık; Ozan Onur Balkanay; Elif Çiftçi; Nevzat Cem Sayılgan; Serkan Burç Deşer; Deniz Göksedef; Suat Nail Ömeroğlu; Gökhan İpek (Cerrahpaşa Medical Journal, 2026)
Objective: Endovenous thermal ablation techniques such as endovenous laser ablation (EVLA) and radiofrequency ablation (RFA) are widely used in the treatment of chronic venous insufficiency. These procedures can be performed under different anesthesia techniques, most commonly local or spinal anesthesia. However, comparative data regarding their perioperative outcomes remain limited. This study aimed to compare the clinical outcomes of endovenous ablation performed under local anesthesia vs. spinal anesthesia in patients with chronic venous insufficiency. Methods: This retrospective study included 102 consecutive patients who underwent EVLA or RFA for chronic venous insufficiency between January 2020 and August 2025. Patients were divided into 2 groups according to anesthesia type: group I (local anesthesia, n = 55) and group II (spinal anesthesia, n = 47). Demographic characteristics, operative time, postoperative complications, and clinical outcomes were evaluated. Venous Clinical Severity Score (VCSS) and Chronic Venous Disease Quality of Life Questionnaire (CIVIQ-20) were assessed preoperatively and postoperatively. Statistical analyses were performed using Statistical Package for the Social Sciences software. Results: The mean operative time was significantly shorter in the local anesthesia group compared with the spinal anesthesia group (52.34 ± 15.6 vs. 64.18 ± 18.55 minutes, P = .007). Postoperative complications including headache, nausea/vomiting, and urinary retention were observed more frequently in the spinal anesthesia group. Deep vein thrombosis occurred in 1 patient in the spinal anesthesia group. Both groups showed significant improvement in VCSS and CIVIQ-20 scores after treatment (P = .001). The 6-month success rates were similar between the groups (97.2% vs. 97.4%, P > .05). Conclusion: Endovenous ablation performed under local anesthesia is associated with shorter operative time and comparable clinical outcomes compared with spinal anesthesia. Both anesthesia techniques appear safe and effective for the treatment of chronic venous insufficiency. Cite this article as: Arapi B, Üstünışık ÇT, Balkanay OO, et al. Local versus spinal anesthesia for endovenous ablation therapy: A comparative study. Cerrahpaşa Med J 2026, 50, 0064, doi: 10.5152/cjm.2026.26064.